Sedative Test of Ethanol Extract of Putri Malu Leaves (Mimosa Pudica Linn.) in Mice (Mus Musculus) With Standardized Herbal Medicine Lelap as Comparison - Jefri Naldi; Indra Ginting; Singgar Ni Rudang; Suci Ramadayanti (Newinera Publisher, 2022)
Dense activity and with increasing age experienced by each community, is one of the causes of decreased sleep quality and trigger sleep disorders. The use of medicinal plants is increasingly in the community such as Sensistive plant leaves. This study aims to determine the sensitive plants and to know the comparison of the work activities of the sensitive plants leaves with a deep sleep. This research was an experimental study with a complete random design in a unidirectional pattern. Test animals used 15 male mice, divided into 5 groups randomly consisting of 3 animals. First Group was given a 0.5% CMC suspension, Second group was given a deep suspension, Third group was given an sensitive plants leaves extract with 5% concentration, fourth group was given an sensitive plants leaves extract of 10% concentration, fifth group was given an sensitive plants leaves extract of 20%. Data obtained by Anova test, followed by Duncan's different test to see the real difference in each experimental group. Administration of sensitive plants leaves extract of 5% leaves did not make a significant difference with sleep, but at a concentration of 10%, 20% gave a significant difference with sedative test on mice that were given a deep sleep. Suspension of sensitive plants leave has a sedative effect on mice, at a concentration of 10%, 20% has the same sedative effect as deep sleep, and research needs to be done on other parts of the sensitive plants leaves that has a stronger sedative effect.